Approximation Algorithm for a System of Pantograph Equations - Sabir Widatalla; Mohammed Abdulai Koroma (Journal of Applied Mathematics)
We show how to adapt an efficient numerical algorithm to obtain an approximate solution of a system of pantograph equations. This algorithm is based on a combination of Laplace transform and Adomian decomposition method. Numerical examples reveal that the method is quite accurate and efficient, it approximates the solution to a very high degree of accuracy after a few iterates.